Condições de trabalho e saúde: Um olhar para os trabalhadores de mineração - Melek , Tangriane Hainiski Ramos (2017)
OBJECTIVE: To analyze the risks and working conditions and their possible relationship with the impacts on quality of life and health conditions in a mining company in the Brazilian South Region. METHODS: This was a descriptive study using qualitative and quantitative methods. The research was carried out at a mining company in the Brazilian Southern Region. Data were collected in four stages: Documentary Analysis - PPRA, PCMSO, workers' records and CAT registration; Interviews with company officials; application of the WHOQOL - brief questionnaire and the accomplishment of the Focal Group. RESULTS: In the analysis of the medical records, 12.06% presented altered carboxyhemoglobin; 10.14% altered chest X-ray and 42.06% altered tone audiometry. Five categories of analysis on the perception of workers emerged and three on the perception of health and safety professionals. Quality of life presented overall positivity with an average score of 78.67 points. Among the domains, the highest score was the Environment (79.4 points) and the lowest was the psychological domain (59.5 points). Age correlated negatively with the psychological domain and social relations, in the age group of 20 to 30 years; in the age group of 31 to 49 years only in the psychological domain and in the age group over 50 years with the physical domain. As for the presence of disease, the domains influenced negatively are the physical and social relations. Most have a good perception about their health; The mean age is 38.21 years and the average service time is 8.85 years. Incomplete primary education predominates and 38.4% presented sensorineural auditory alterations. Among those exposed to smoking and alcohol consumption the prevalence ratio: with ages above 40 years and exposure to noise above 80 dBA, for the risk of hearing loss is 1.5 times higher. CONCLUSIONS: It was verified that the workers perceive that their work environment is insecure. It was observed that the miners have a good perception of their Quality of Life, according to the average general score of 78,67. Among the risks, exposure to noise among the miners surveyed is constant, as most of these workers are exposed to levels above 80dBA. There is also a high prevalence of hearing loss, which corroborates the high level of exposure.